Transformational leadership for the inclusion of sexual and gender diversity in Secondary Education. The vision of school leadership teams - Fernández-Jiménez, Antonio; Cascales Martínez, Antonia; Gomariz Vicente, Mª Ángeles (Revista Complutense de Educación, 2024)
Sexual and gender diversity requires strategies that allow its visibility and inclusion within Secondary Education centres in order to offer an adequate response to deal with this diversity and contribute to the elimination of homophobic and transphobic attitudes in the classroom. In this way, it is possible to study the influence of the leadership developed by the people who run the educational centres to deal with this diversity. A quantitative research study was developed with a questionnaire designed ad hoc in which 123 secondary school principals from the national territory participated through a non-probabilistic intentional sampling. The results show how gender, age and field of teaching knowledge from school heads are factors that influence to develop a transformational and distributed leadership model. Here, the leader motivates and fosters innovation among teachers under a cooperative working approach among all members of the community. The conclusion of the study reflects the need to develop a cooperative leadership model among teachers and with the whole educational community in order to develop a change in favour of an adequate attention to sexual and gender diversity in the classroom.
Keywords: Head of school; education; inclusive education; leadership; sexuality